Un monastero sul mare Ricerche archeologiche a San Quirico di Populonia (Piombino, LI)/ A Monastery by the Sea : Archaeological Research at San Quirico di Populonia (Piombino, LI) - Bianchi, Giovanna (Biblioteca di Archeologica Medievale, 2016)
The remains of the monastery of San Quirico stand on the slopes of Poggio Tondo, a hill not far from the ancient city of Populonia. They overlook the Tyrrhenian Sea, dotted with the islands of the Tuscan archipelago. Field research at this site, carried out in the first decade of the new millennium by two different teams, from Siena University and Venice's Ca' Foscari University, respectively, was part of ongoing efforts to expand the Baratti-Populonia Archeological Park, and to further explore the features present within it. This volume contains the results of this research work: a scientific publication of the excavation, and a critical analysis of the material found. Processing of the data collected during these investigations, together with a re-reading of written documentation, has made it possible to piece together the complex history of this important monastery, in a totally new narration. In this narration, the history of the monastery, and of the features which existed prior to it, are closely interwoven with the history of the promontory of Populonia and the surrounding area, ultimately producing a new overview which sets out the historical boundaries of this area, between Late Antiquity and the modern era.